Another Report of Acalculous Cholecystitis in a Greek Patient with Infectious Mononucleosis: A Matter of Luck or Genetic Predisposition? - Theocharis Koufakis; Ioannis Gabranis (Case Reports in Hepatology)
We here report a case of a young, male patient who presented with jaundice and was diagnosed with acalculous cholecystitis during the course of a primary Epstein-Barr Virus (EBV) infection. The coexistence of cholestatic hepatitis and acalculous cholecystitis in patients with infectious mononucleosis is extremely uncommon and only few cases can be found in the literature. Moreover, almost one-fourth of the total reports of this rare entity are coming from Greece. Whether this is a result of physicians’ high index of suspicion due to previous reports or a consequence of genetic predisposition is an issue that deserves further investigation in the future. More studies are required in order to clarify the pathophysiological and genetic backgrounds that connect acalculous cholecystitis and EBV infection.